The Influence of Attitude, Locus of Control, and Creativity on Entrepreneurial Tendency - Feibry Feronika Wiwenly Senduk (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
The entrepreneurial tendency is an interest of someone in entrepreneurs. This research was aimed at finding the effects of attitude, locus of control, and creativity on entrepreneurial tendency by using the linear regression analysis test as the method of data analysis. The samples were taken from the population of lecturers. The data were taken from the samples using questionnaire distribution and later were used to measure the attitude, locus of control, and lecturer’s creativity. Linear regression analysis test was conducted with normalization, homoscedasticity, multicollinearity, and path analysis to describe the lecturer’s strengths and weaknesses on the entrepreneurial tendency.